Interrogating interplay effect in radiotherapy with a highly sensitive 2-D moving detector - Yip, Qiu Mei (Nanyang Technological University, 2023)
Interplay effect has been a challenging problem to deal with in the field of medical radiotherapy. The presence of interplay effect can pose many difficulties as well as deviations in the treatments delivered to the patients. For the purpose of this study, patients receiving the stereotactic body radiation therapy (SBRT), where hypofractionation and smaller treatment margins are employed, will be considered. For patients receiving SBRT, the tendency for interplay effect poses a higher risk to them. Hence, the need to investigate and quantify the interplay effect and its relation will be further studied. Interplay effect can be quantified that is using patient specific quality assurance - gamma analysis (2%/2mm and 3%/3mm) and hot spots analysis. It is also crucial to study how interplay effect correlates to the plan complexity. In this study, there are adequate quantifications for the interplay effect with gamma passing rate as well as hot spot values. That is, as interplay effect increases, the gamma passing decreases, in turn means delta change in gamma passing increases. Whereas for hot spots value, when the interplay effect is larger, the hot spots values also increases. Upon this quantification, the study of its effect on plan complexity was studied. It is found that CoA, LSV as well as MAD has relationship with the interplay effect.